Exploring the Impact of Patient and Public Involvement in a Cancer Research Setting. (January 2014) - Thompson, Jill; Bissell, Paul; Cooper, Cindy L.; Armitage, Chris J.; Barber, Rosemary
An enduring theme in the literature exploring patient and public involvement (PPI) in research has been the focus on evaluating impact, defined usually in terms of participants' practical contribution to enhancing research processes. By contrast, there has been less emphasis on the perspectives and experiences of those involved in PPI. Drawing on qualitative data with people involved in the National Cancer Research Network in the United Kingdom, we report on what motivated participants to get involved and their experiences of involvement in this setting. We highlight how those involved in PPI often espoused the notion of the "good citizen, " with PPI in research being a natural extension of their wider civic interests. However, our findings also highlight how PPI was an important resource, utilized by participants to make sense of living with chronic illness. We suggest that PPI in research also offers spaces for the reconfiguration of self and identity.